Pemilihan Presiden Dan Penciptaan Mekanisme 'Checks and Balances': Menuju Penciptaan Sistem Presidensial Murni - Afan Gaffar (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2000)
The attempt to question the legitimacy of President Abdurrahman Wahid has led to reemergence of the idea of having a direct election for the filling the President post, instead of having an indirect election, namely through the People's Consultative Assembly (Majelis Permusyawaratan Rakyat or MPR). This article rejects the idea of engaging in a constitutional reform on a reactive for a short terms interest. If we are committed to have a direct election for recruiting president, we have to do it thoroughly and comprehensively based on a well-chosen design. For that purpose, this article outlines some mechanisms for direct election for the president. We have to decide which mechanism fit to Indonesian political life. More whichever mechanism we choose it has to fit with the idea of establishing check and balances.